Investigation on cavitation behavior of ultrahigh molecular weight polyethylene during stretching in wet process and dry process. (16th September 2021) - Wu, Yunqi; Yang, Feng; Cao, Ya; Xiang, Ming; Kang, Jian; Wu, Tong; Fu, Qiang
Abstract: Nowadays, the rapid development of lithium-ion batteries (LIBs) leads to an urgent demand for the separator with excellent mechanical and electrochemical performances. In this work, the ultra-high molecular weight polyethylene (UHMWPE)/liquid paraffin (LP) gel film and the film after extraction of LP are prepared respectively. Due to the identical crystalline structure but different content of free volume pores, the pore formation mechanism during stretching in wet process and dry process could be accurately distinguished by scanning electron microscope and in-situ small-angle X-ray scattering. It is found that since the free volume pores in amorphous phase of UHMWPE have been filled with LP, the cavitation phenomenon is suppressed completely during stretching in wet process. The porosity of membrane after biaxial stretching is just relative to the LP content instead of the draw ratio and a unique laminated structure is created along the thickness direction. On the contrary, after extraction of LP, the free volume pores in amorphous region could act as nuclei to initiate intensive cavitation effect in dry process, leading to the significant increase of pore size and porosity of membrane with the draw ratio. Furthermore, the separator made from dry process displays better electrochemical performances but worse mechanical properties than that obtained from wet process. Therefore, it is reasonable to believe that the LIBs separator with optimal pore structure and excellent properties could be developed by combining the advantages of dry process and wet process. Graphical abstract: Image 1 Highlights: Free volume pores could act as nuclei to initiate cavitation in dry process. Cavitation is suppressed when stretched in wet process. Separator made from dry process has large pore size and high porosity. Separator produced by wet process has uniform pore size distribution.